Proceedings of Eurosensors 2017, Paris, France, 3–6 September 2017 2017
DOI: 10.3390/proceedings1040395
|View full text |Cite
|
Sign up to set email alerts
|

Contactless Interrogation System for Capacitive Sensors with Time-Gated Technique

Abstract: This paper presents a measurement technique and system for the contactless interrogation of capacitive sensors via electromagnetic coupling. The interrogation unit employs a primary coil to periodically excite the capacitive sensor connected to a secondary coil forming an LC resonant circuit. When the excitation to the primary coil is switched off the damped response of the LC circuit is detected. As a fundamental advantage compared to techniques based on reflected impedance, this approach ensures that the rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…6. (a) [39], [40]. The basic operating principle of the time domain measurement technique is depicted in Fig.…”
Section: B Time Domain Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…6. (a) [39], [40]. The basic operating principle of the time domain measurement technique is depicted in Fig.…”
Section: B Time Domain Measurementmentioning
confidence: 99%
“…Nopper et al showed that instead of measuring the phase, the measurement of the real part of equivalent impedance does not have a dependence on the k and hence, the wireless measurement distance [37], [38]. On the other hand, time domain measurement of the sensor utilises the damped decay response to extract the resonance frequency and quality factor of the sensors [39], [40]. Analytical modeling of the LC resonant sensors in the time domain shows that measurement of the resonant frequency is independent of the wireless interrogation distance.…”
Section: Introductionmentioning
confidence: 99%
“…This plasmonic sensor can detect changes in the permittivity of the oil caused by the modification of the chemical properties of the lubricant. It is also worth noting that Masud et al [32] presented a contactless interrogation technique and system for capacitive sensors via electromagnetic coupling. The sensor unit was composed of the capacitive sensor connected to a tuning capacitor and a coil forming an LC resonant circuit.…”
Section: Introductionmentioning
confidence: 99%